2016
DOI: 10.1186/s12910-016-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for ELSI early career researchers

Abstract: BackgroundOver the past 25 years, there has been growing recognition of the importance of studying the Ethical, Legal and Social Implications (ELSI) of genetic and genomic research. A large investment into ELSI research from the National Institutes of Health (NIH) Human Genomic Project budget in 1990 stimulated the growth of this emerging field; ELSI research has continued to develop and is starting to emerge as a field in its own right. The evolving subject matter of ELSI research continues to raise new resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…3 Considering this review, the perceived barriers among early-career epidemiologists appear to be very similar to those among general post-doctoral academics. In addition, similar barriers have been suggested among researchers in endocrinology, 8 genetics, 9 and psychology. 10 The present study showed that early-career epidemiologists share common barriers with early-career people in other fields, and that early-career epidemiologists around the world share common barriers to their career progression.…”
Section: Summary Of Discussion At the Meetingmentioning
confidence: 64%
See 1 more Smart Citation
“…3 Considering this review, the perceived barriers among early-career epidemiologists appear to be very similar to those among general post-doctoral academics. In addition, similar barriers have been suggested among researchers in endocrinology, 8 genetics, 9 and psychology. 10 The present study showed that early-career epidemiologists share common barriers with early-career people in other fields, and that early-career epidemiologists around the world share common barriers to their career progression.…”
Section: Summary Of Discussion At the Meetingmentioning
confidence: 64%
“…3 , 4 Identifying these barriers is important when considering beneficial support for career progression. 5 – 7 Past findings suggest area-specific barriers among early-career researchers in endocrinology, 8 genetics, 9 and psychology. 10 However, little is known about barriers faced by early-career epidemiologists.…”
mentioning
confidence: 99%
“…For example, in 2004, NHGRI collaborated with the DOE and the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) to establish the first four CEERs. 61 , 63 In 2020, it continued the funding for three CEERs (see Table 4 ) using a limited competition request for proposals (renewal of current CEERs only) with the indication that “NHGRI plans to maintain the CEER program at approximately its current level of funding through FY 2023.” 64 In 2019, it funded the Center for ELSI Resources and Analysis (CERA) to build the community ELSI researchers and provide a web-based platform to enhance the production, sharing, and use of ELSI research (for CERA rationale, see Oliver and McGuire, 65 Kaye et al, 66 and Bell et al 67 ). Although a small portion of the budget, the program has also provided formal support for ELSI studies embedded in large genomics initiatives sponsored by other NHGRI divisions such as the CSER Consortium, eMERGE, the Human Microbiome Project, the Wellcome Trust/NIH H3Africa Initiative, and the NBSeq initiative, as well as supplements to other NIH grants with ELSI components.…”
Section: Recent Nhgri Elsi Funding Prioritiesmentioning
confidence: 99%
“…Early-career researchers in the ELSI field face particular problems of isolation from disciplinary support structures, as the article by Bell et al reports [34], based on a workshop for ELSI researchers at the Translation in Medicine conference. This workshop discussed the potential opportunity to use web 2.0 technologies, such as the ELSI 2.0 workspace currently provided through the Global Health network [35], to transform academic support structures and address some of the challenges faced by ELSI ECRs, by helping to facilitate mentoring and support, access to resources and new accreditation metrics.…”
Section: Ethical Legal and Social Issues In Translationmentioning
confidence: 99%